Говорещи скали, илюзорни звуци и проекции на отвъдния свят : Акустиката на свещените места като магическo средство в шаманските култури - Shpinitskaya, Julia; Rainio, Riitta (Университетско издателство Епископ Константин Преславски, 2025)
The archaeoacoustic team of the University of Helsinki has been studying how sacred sites in Northern Europe, used by shamanic cultures since prehistoric times, are home to remarkable acoustic properties. This chapter focuses on natural-site acoustics as a magic tool in ritual practices. Based on our acoustic measurements as well as experimental sound tests carried out during in situ studies of prehistoric and historic sacred sites in Finland, we discuss possible sound media (voice, instruments, noise), performing techniques and methods of sound production used at the sites. While the acoustic study of the sacred sites is at the core of our research, we also discuss the visual aspects and visual phenomena observed at the sites during our fieldwork. Our attempt to restore the sound culture of shamanism associated with the hosting sites and their sound potential profoundly rests on ethnographic research of the Finno-Ugric peoples, predominantly the Sámi and the Finns. The end result of this ethnographic and practical research study is our interpretation of the shamanic ritual practices as seen through the prism of the miraculous acoustic illusions and visual appearances created by the sacred sites. Peer reviewed